Increased air temperature decreases high-speed, but not total distance, in international field hockey - James, C. A.; Willmott, A. G. B.; Dhawan, A.; Stewart, C.; Gibson, O. R. (Temperature, 2022)
This study investigated the effect of heat stress on locomotor activity within international field hockey at team, positional and playing-quarter levels. Analysis was conducted on 71 matches played by the Malaysia national men`s team against 24 opponents. Fixtures were assigned to match conditions, based on air temperature [COOL (14 ± 3°C), WARM (24 ± 1°C), HOT (27 ± 1°C), or VHOT (32 ± 2°C), p < 0.001]. Relationships between locomotor metrics and air temperature (AIR), absolute and relative humidity, and wet bulb globe temperature (WBGT) were investigated further using correlation and regression analyses. Increased AIR and WBGT revealed similar correlations (p < 0.01) with intensity metrics; high-speed running (AIR r = -0.51, WBGT r = -0.45), average speed (AIR r = -0.48, WBGT r = -0.46), decelerations (AIR r = -0.41, WBGT r = -0.41), sprinting efforts (AIR r = -0.40, WBGT r = -0.36), and sprinting distance (AIR r = -0.37, WBGT r = -0.29). In comparison to COOL, HOT, and VHOT matches demonstrated reduced high-speed running intensity (-14-17%; p < 0.001), average speed (-5-6%; p < 0.001), sprinting efforts (-17%; p = 0.010) and decelerations per min (-12%; p = 0.008). Interactions were found between match conditions and playing quarter for average speed (+4-7%; p = 0.002) and sprinting distance (+16-36%; p < 0.001), both of which were higher in the fourth quarter in COOL versus WARM, HOT and VHOT. There was an interaction for "low-speed" (p < 0.001), but not for "high-speed" running (p = 0.076) demonstrating the modulating effect of air temperature (particularly >25°C) on pacing within international hockey. These are the first data demonstrating the effect of air temperature on locomotor activity within international men`s hockey, notably that increased air temperature impairs high-intensity activities by 5-15%. Higher air temperatures compromise high-speed running distances between matches in hockey.